English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

you can write:
xlnx = lnx / (1/x)
in this way you can use L'Hopital's rule,
and take the derivative of the numerator and divide it by de derivative of the denumerator:

lim x lnx = lim lnx / (1/x) = lim 1/x / (-1/x^2) = lim -x =0
x-->0

2006-09-18 15:13:25 · answer #1 · answered by Anonymous · 1 1

this is of the from 0 * inf

lim x->0 x ln x
= x->0 ln x/ (1/x)

this is of the form inf/inf
differentiate both num and denom
(1/x) /(-1/x^2) = -x =0

2006-09-19 03:36:40 · answer #2 · answered by Mein Hoon Na 7 · 0 0

the value of natural log zero is undefined, but lnX approaches zero as x approaches zero. Furthermore, you are multiplying the natural log of a small number by that same small number, hastening its approach to zero; but the limit is still zero all the same

2006-09-18 14:53:02 · answer #3 · answered by davidosterberg1 6 · 0 3

fedest.com, questions and answers